(3JhGdi GdefM aj CSeGA KeGQ GdfNd hQJHI GdHdMs - (3HOQ GdOjf eMeO Hf jMji Hf YeQ GdbQGai GdeGdcjs
(3ChdgG (B:s
(3hHYO , agPg QSGdI SejJgG HJhGdi GdefM ai CSeGA KeGQ GdfNd hQJHI GdHdM , OYGfi Edi Pdc YfOeG LQi GdcdGe ai YHGQI GdbGehS s
(3BNQgG (B:s
(3hGdRgQ GHJOGA GdfNd hGUaQGQg hGMeQGQg hLGA ai HYV QhGjGJ GdMOjK hbGd CHh RjO RgjQ s
(3Vef eLehY s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B141s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 s
Keywords: (3GddZIs